Impact of Physical Workload and Mental Workload on Nurse Performance: A Path Analysis - Pamungkas, Rian Adi; Ruga, Forestriano Bayu Putra; Kusumapradja , Rokiah (Alta Dharma Publisher, 2022)
Background. Nurse performance is an important factor in hospitals. Studies on nurse performance are required to improve the quality of hospital services. Objective. This study aims to determine the effect of physical and mental workloads on nurse performance, with burnout as an intervening factor. Method: This associative quantitative research uses primary data obtained through a survey of nurses at the inpatient unit of Bhakti Asih General Hospital, Tangerang. The survey was conducted by distributing questionnaires to 84 nurses using a modification of the National Aeronautics and Space Administration – Task Load Index, Maslach Burnout Inventory – Human Services Survey, and Individual Work Performance Questionnaire. The variables were analyzed using the path analysis method. Results: The results show no significant effect of physical and mental workloads on nurse performance, with burnout as an intervening factor. There was a negative significant effect of physical workload on nurse performance (? = -0.309, sig. = 0.004), as well as mental workload on nurse performance (? = -0.340, sig. = 0.009). There was a positive significant effect of physical workload on burnout (? = 0.267, sig. = 0.002), as well as mental workload on burnout (? = 0.607, sig. = 0.000). There was no significant effect of burnout on nurse performance (? = -0.159, sig. = 0.224). Conclusion: In conclusion that physical and mental workload impact on nurses’ performance